Business Contract For Commercialization Of Research Results Funded By Universities For The Development Of Edutourism In Bangkalan - Melati, Santi Rima; Nugroho, Lucky Dafira; Wahyuliana, Ida (LPPM Universitas Trunojoyo Madura, 2024)
The article discusses the potential of Indonesia's abundant natural resources as a foundation for achieving equitable prosperity, as mandated by the 1945 Constitution. It emphasizes the importance of managing these resources through the development of science and technology to enhance national competitiveness. The research highlights the need for effective commercialization of research outcomes, which can include theories, ideas, and practical products, to create economic value and benefit society. The study identifies an ideal model for business contracts in the commercialization of research results, advocating for a proportional profit-sharing agreement. This model ensures fairness between researchers and funding entities, promoting equitable rights and obligations. The research methodology is empirical, focusing on social phenomena and realities within the community, and involves interviews and data collection from various tourism destinations in East Java. The findings suggest that the commercialization of research results, particularly in the context of edutourism, requires clear contractual agreements to delineate the rights and responsibilities of all parties involved. This approach aims to foster sustainable tourism development while maximizing the economic benefits derived from research innovations.